ANALISIS PENGARUH KOMPETENSI SOSIAL GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI DI SMAN 1 KATEMAN (Studi Kasus: Siswa Kelas X B SMAN 1 Kateman) - Mariyana, Mariyana; Hefni; Yanti Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by teachers who are less able to interact well, from the results of observations made it appears that students are still less enthusiastic about learning when the teacher is unable to communicate well. This study aims to analyse how the influence of teacher social competence on student learning motivation in Sociology subjects at SMAN 1 Kateman. This research uses Cognitive theory from Jerome S. Bruner, cognitive learning theory This research uses a quantitative approach. This type of research is regression. The sampling technique is total sampling technique. Data collection methods in this study using questionnaire observation and document study. Data analysis methods used with descriptive analysis and simple linear regression analysis. In this study, the instruments used were observation guidelines and questionnaires. The results showed that the teacher's social competence had a significant effect on student learning motivation in Sociology subjects at SMAN 1 Kateman. This can be seen from the coefficient value of 0.724. This coefficient value is significant because the tcount value is 5.213> ttable 1.69092 with a significant level of 0.000 <\{mathbitα = 0,05. This shows that teacher social competence has a significant effect on student learning motivation. The higher the increase in teacher social competence, the higher the student learning motivation, so if the teacher's social competence is low, the student learning motivation will also be low or down. The magnitude of the influence of the independent variable on the dependent variable is 45.2%. This means that the independent variable of teacher social competence is able to explain the dependent variable of student learning motivation by 45.2%.